PENGARUH THINK PAIR SHARE TERHADAP HASIL BELAJAR MATEMATIKA DI KELAS V SEKOLAH DASAR - Fitri, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to analyze whether there is an effect of using Think Pair Share the learning outcomes of students in class V Elementary School 02 Kubu Raya Sungai Raya. This study used an experimental method quasy type of experiment. The population in this study were all fifth grade students of State Elementary School 02 Kubu Raya Sungai Raya which consists of two classes, namely the VA and V B. Samples were students of class VA (experimental group), totaling twenty-six students and VB (control group) totaling twenty-eight students. Based on the analysis data was obtained by the average post-test control class average of 44.50 and a post-test experimental class 67.96. The results of hypothesis by using t-test (polled variants) obtained t = 5.1902 for df = 52 and Î± = 5% is obtained t_tabel at 1.6788 which means t_test > t_tabel (5.1902 > 1.6788), then Ha accepted , So, it can be concluded that there are effects of the use of Think Pair Share toward student learning outcomes. Keywords :Think Pair Share, student learning outcomes